2015
DOI: 10.4236/health.2015.72022
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Educational Video to Promote Self-Efficacy in Preventing Childhood Diarrhea

Abstract: The aim of this study was to evaluate and to validate an educational video to promote maternal self-efficacy in preventing childhood diarrhea with women assisted in a health unit. Validation study, developed with 17 mothers whose children were under five years old, was analyzed on scenes of an educational video according to the validity of appearance (clarity/comprehension) and of content (relevance). The scenes were considered clear and comprehensive with a perceptual above 70% and with an average of 96.9% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 8 publications
1
17
0
5
Order By: Relevance
“…Results of previous researches, which served as a basis for elaborating the survey on the primary care for promoting maternal self-efficacy in preventing childhood diarrhea, showed that mothers presented similar characteristics to those from this study, such as low education and families consisting of more than three members (7,12) . These aspects reflect the reality of part of the Brazilian population, so that the educational primer emerges as a valid and reliable material both for economically disadvantaged families and those with greater socioeconomic conditions, since the primer is understandable to the lowest stratum of the population, it will also be for the highest.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Results of previous researches, which served as a basis for elaborating the survey on the primary care for promoting maternal self-efficacy in preventing childhood diarrhea, showed that mothers presented similar characteristics to those from this study, such as low education and families consisting of more than three members (7,12) . These aspects reflect the reality of part of the Brazilian population, so that the educational primer emerges as a valid and reliable material both for economically disadvantaged families and those with greater socioeconomic conditions, since the primer is understandable to the lowest stratum of the population, it will also be for the highest.…”
Section: Discussionsupporting
confidence: 66%
“…We also highlight the fact that some suggestions have not been accepted also occurred in other studies, being necessary to assess whether the mothers' suggestions are relevant to the purpose of the educational material (12) .…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations